2007
DOI: 10.1063/1.2760205
|View full text |Cite
|
Sign up to set email alerts
|

Quasielastic neutron scattering experiments including activation energies and mathematical modeling of methyl halide dynamics

Abstract: Quasielastic neutron scattering experiments were carried out using the multichopper time-of-flight spectrometer V3 at the Hahn-Meitner Institut, Germany and the backscattering spectrometer at Forschungszentrum Julich, Germany. Activation energies for CH(3)X, X=F, Cl, Br, and I, were obtained. In combination with results from previous inelastic neutron scattering experiments the data were taken to describe the dynamics of the halides in terms of two different models, the single particle model and the coupling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Methyl rotational attempt frequencies are generally found to lie in the range of 2–5 meV, so this value is also quite a bit lower than expected. A possible origin for the lower attempt frequency in M-POSS would be the presence of methyl–methyl coupling in the M-POSS crystal structure . For example, QENS studies of methyl halides have found that both methyl fluoride (CH 3 F) and methyl chloride (CH 3 Cl) have attempt frequencies that lie below those of the bromide and iodide.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Methyl rotational attempt frequencies are generally found to lie in the range of 2–5 meV, so this value is also quite a bit lower than expected. A possible origin for the lower attempt frequency in M-POSS would be the presence of methyl–methyl coupling in the M-POSS crystal structure . For example, QENS studies of methyl halides have found that both methyl fluoride (CH 3 F) and methyl chloride (CH 3 Cl) have attempt frequencies that lie below those of the bromide and iodide.…”
Section: Resultsmentioning
confidence: 63%
“…A possible origin for the lower attempt frequency in M-POSS would be the presence of methyl−methyl coupling in the M-POSS crystal structure. 63 For example, QENS studies 63 of methyl halides have found that both methyl fluoride (CH 3 F) and methyl chloride (CH 3 Cl) have attempt frequencies that lie below those of the bromide and iodide. This was attributed to coupling between methyl rotations on different molecules.…”
Section: Resultsmentioning
confidence: 99%
“…7 Only the activation energy is higher than the recently reported experimental value of 13.9 meV but still within the reported experimental error of Ϯ0.7 meV. 8 In addition, methyl fluoride shows the most complex density of states of all of the halides. In particular librations around the CH 3 F bond axis show lower amplitudes than those perpendicular to it, and this constant variation of distance between two molecules could alter the potential parameters and thus potentially explain the difference between the calculated and observed split of the tunneling sublevels.…”
Section: Resultsmentioning
confidence: 70%
“…9 In general, the dynamics of rotating CH 3 groups can be described by a mean field theory, which is commonly known as the single particle model or SPM. 10 Recent quasielastic neutron scattering experiments 8 confirmed that the SPM is a suitable model to describe the dynamics and associated transitions such as tunneling and librational transitions as well as activation energies of the bromide and iodide. A thorough statistical analysis of the dynamics of the chloride and the fluoride in particular indicated that the SPM would not be the appropriate model to accurately describe the dynamics of those two molecules.…”
Section: Rotational Dynamics and Coupling Of Methyl Group Rotations Imentioning
confidence: 89%
See 1 more Smart Citation